Reducing job hopping intentions through personal psychological aspects - Amruloh, Dedeng; Imbari, Salman; Fitriyani, Fitriyani (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2023)
This study aims to investigate the impact of personal psychological factors, such as work-life balance and job satisfaction, on the job-hopping intentions of millennials. The research employs a quantitative approach, and the study population consists of millennial employees working in Purwakarta Regency. The data was collected using non-probability and accidental sampling techniques, with a total sample size of 100 employees. Multiple linear regression analysis was used to analyze the data, with the help of the IBM SPSS Statistics 26 application. The findings of this research can help companies understand the reasons behind employee turnover, including voluntary turnover, such as job-hopping. By understanding the psychological aspects of their employees, companies can reduce job-hopping and other forms of turnover. The study provides evidence that taking a personal psychological approach to millennial employees can help reduce job-hopping intentions, which is crucial for companies to minimize losses due to turnover.